2022
DOI: 10.3389/fgene.2022.797796
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Important Genes Involved in the Sex-Differentiation Mechanism of Oriental River Prawn, Macrobrachium nipponense, During the Gonad Differentiation and Development Period

Abstract: Identification of important genes, involved in the gonad differentiation and development, plays essential roles in the establishment of the artificial technique to regulate the process of testis development in M. nipponense. In this study, we aimed to determine the sensitive period of gonad differentiation and development through hematoxylin and eosin (HE) staining. The important genes involved in the gonad differentiation and development of M. nipponense were then identified through transcriptome profiling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The AX-249,988,993 (LG31, pos: 26.457 cM) and AX-249,687,820 (LG31, pos: 28.246 cM) SNPs intercepted the oplophorus-luciferin 2-monooxygenase and serine/arginine repetitive matrix protein genes, respectively. Although these genes are not directly related to sex determination, some studies shown that they are expressed in the gonads of crustaceans, such as Macrobrachium nipponense [ 33 ] and Penaeus monodon [ 34 , 35 ]. Another interesting gene, spermine oxidase , was found close to the AX-249,610,151 SNP (~ 20Kb downstream).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AX-249,988,993 (LG31, pos: 26.457 cM) and AX-249,687,820 (LG31, pos: 28.246 cM) SNPs intercepted the oplophorus-luciferin 2-monooxygenase and serine/arginine repetitive matrix protein genes, respectively. Although these genes are not directly related to sex determination, some studies shown that they are expressed in the gonads of crustaceans, such as Macrobrachium nipponense [ 33 ] and Penaeus monodon [ 34 , 35 ]. Another interesting gene, spermine oxidase , was found close to the AX-249,610,151 SNP (~ 20Kb downstream).…”
Section: Resultsmentioning
confidence: 99%
“…However, oplophorus-luciferin 2-monooxygenase and serine/arginine repetitive matrix protein (SRRM1) genes were intercepted by significant SNPs. The first gene was downregulated at both the PL15 and PL25 stages in the gonadal tissues of M. nipponense [ 33 ]. Although its specific function is still unclear, this gene was found to be related to metabolic and extra cellular matrix processes in other crustacean species [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on sequence annotation and literature report [ 3 , 24 , 25 , 26 ], sex-related genes were identified in mRNA expression profiles ( Table S7 ). The expression levels of IAG and membrane-anchored androgenic gland-specific factors ( MAG ) showed similar trends.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the glycolysis/gluconeogenesis pathway is involved in most biological processes, and has been shown to be an important pathway participating in male development in M. nipponense. In previous transcriptome studies in M. nipponense, the expression of many genes in the glycolysis/gluconeogenesis pathway was found to vary during the post-larval developmental stages 5 (PL5) to PL25, the sensitive periods for gonad development [34]. In addition, after ablation of the eyestalk, which is a key organ for secreting many hormones during male sexual development in crustaceans, the glycolysis/gluconeogenesis pathway is also one of the main sources of enrichment of the DEGs in the testes and androgenic gland of M. nipponense [35].…”
Section: Discussionmentioning
confidence: 99%